Chemical compositions of Passiflora edulis seeds oil collected in Vietnam - Cuong, To Dao; Phuong, Doan Lan; Anh, Nguyen Van Tuyen; Khanh, Pham Ngoc; Huong, Tran Thu; Cuong, Nguyen Manh (Vietnam Journal of Science and Technology, 2019)
The present research was aimed to study the chemical compositions of Passiflora edulis Sims seeds oil, including the fatty acid profiles, contents of tocopherols, sterols, and triglycerides. The seeds oil yield is 24.88% by using Soxhlet method. Passiflora edulis seeds oil showed high levels of unsaturated fatty acids (89.25%) with main ingredient linoleic acid (w-6, 66.94%) and oleic acid (w-6, 18.86%). Tocopherols (18.04 mg/kg), sterols (2935.35 mg/kg) and triglycerides (monomere TAG, 74.11%) are also determined by using IOC and ISO methods, respectively. The findings demonstrate that P. edulis seeds oil could be used beneficially in the food and cosmetic industries.